DEVELOPMENT OF ICT-BASED WORKSHEET ON STEM-INTEGRATED TO INCREASE KNOWLEDGE, DATA LITERACY, AND TECHNOLOGY LITERACY OF HIGH SCHOOL STUDENTS - Mutiara Dier; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2022)
The development of education cannot be separated from the development of the current Industrial Revolution 4.0. One of the chops that can answer the industrial revolution is data literacy and technological literacy. The use of ICT-based teaching materials is needed in learning in this era. Correspondingly, stem integration will improve new literacy skills. However, in preliminary studies, the lack of ICT-based worksheet use in the learning process. The solution to this problem is to create STEM-integrated ICT-based worksheets. The purpose of this study is to determine the effectiveness of ICT-based worksheets in effective STEM integration work and energy teaching materials to improve students' knowledge, data literacy, and technology literacy. This type of research is Research and Development (R&D) according to the Plomp model. The data obtained from this study is the result of expert validation. Data analysis techniques using descriptive statistical analysis with Aiken's V validation. The validation results of Aiken's V stated that the average of 0.80 had a high coefficient of Aiken's V criteria. This result was obtained from an average of three expert validators. Thus, an ICT-based worksheet, a STEM-integrated work, and energy material to improve the data literacy and technological literacy of SMA students is declared valid and suitable for learning. It is hoped that this worksheet can be a reference for further research to improve the quality of learning to answer the challenges of the upcoming revolution era